(untitled) (ESMAT Magazine, 2026)
Extreme weather events have intensified globally, posing significant challenges to the adaptive capacity of states. Under the Paris Agreement, Brazil has committed to strengthening climate resilience and reducing socio-environmental vulnerabilities. This study examines the cross-cutting impacts of climate change on a global and local scale, with an emphasis on the 2024 disaster that affected the Taquari-Antas Basin in Rio Grande do Sul. The methodology is qualitative, based on the analysis of international documents, particularly from the IPCC and the World Meteorological Organization, as well as institutional reports related to regional impacts. The results indicate the increasing severity of climate-related effects, such as rising temperatures, extreme events, environmental losses, food insecurity, and forced displacement. At the local level, the 2024 disaster resulted in 184 deaths, widespread economic losses, severe damage to agriculture and livestock, increased health risks, and destruction of homes. These impacts highlight structural vulnerabilities and raise important legal implications, including the advancement of climate litigation. Of particular note is the Taquari-Antas Public Civil Action, which seeks recognition of state responsibility for damages resulting from the extreme event and the fulfillment of constitutional duties of environmental protection and risk management. It can be concluded that the regional crisis reflects the materialization of global risks associated with climate change and reinforces the need to improve public policies, legal instruments, and governance structures to address recurring climate emergency scenarios.